Súmula vinculante e ratio decidendi: uma abordagem empírica a respeito de redesenho institucional e cultura jurídica - Glezer, Rubens Eduardo (2011)
The 2004 Brazilian Judiciary Reform is part of a long process of political attempts to create changes that were not produced spontaneously by the legal culture. The súmula vinculante is a great example of such process, since is a legal institute aimed to solve persistent problems that came from the absence of a legal culture of precedents in Brazil. However, the own effectiveness of the institute depends on the adequate use of a precedents rationale, since the clarity of the binding rulings depends on the clarity of the ratio decidendi of the respective precedents. By the analysis of the legislative debates that created the súmula vinculante, as well of the approval proceedings of the binding rulings related to criminal law issued until the end of 2010, it was researched precisely how the Brazilian Supreme Court managed to handle such institute that conflicts with the traditional way of providing grounds to judicial decisions and of conceptual rather than factual relation between past decisions.